1997
DOI: 10.1183/09031936.97.10061380
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for chronic obstructive pulmonary disease

Abstract: Cigarette smoking is the major risk factor for chronic obstructive pulmonary disease (COPD). However, only a minority of cigarette smokers develop symptomatic disease. Studies of families and twins suggest that genetic factors also contribute to the development of COPD. We present a detailed literature review of the genes which have been investigated as potential risk factors for this disease.The only established genetic risk factor for COPD is homozygosity for the Z allele of the α 1 -antitrypsin gene. Hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(82 citation statements)
references
References 202 publications
0
74
0
8
Order By: Relevance
“…Cigarette smoking is the most widely recognized environmental contributor to lung function decline. Occupational exposures, air pollution, a history of respiratory infections and allergens also contribute to impaired pulmonary function, but the contribution of genetics in determining lung development and pulmonary diseases also appears to be substantial [Sanford et al, 1997;Chen et al, 1996;Coultas et al, 1991]. A small proportion of patients with emphysema can attribute their lung dysfunction to a homozygous mutation in the alpha-1-antitrypsin gene that causes a deficiency in the enzyme inhibitor [Tobin et al, 1983], but genes influencing commonly occurring pulmonary dysfunction are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is the most widely recognized environmental contributor to lung function decline. Occupational exposures, air pollution, a history of respiratory infections and allergens also contribute to impaired pulmonary function, but the contribution of genetics in determining lung development and pulmonary diseases also appears to be substantial [Sanford et al, 1997;Chen et al, 1996;Coultas et al, 1991]. A small proportion of patients with emphysema can attribute their lung dysfunction to a homozygous mutation in the alpha-1-antitrypsin gene that causes a deficiency in the enzyme inhibitor [Tobin et al, 1983], but genes influencing commonly occurring pulmonary dysfunction are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of NSPs to COPD was first evidenced by the observation that patients lacking ␣1-Pi, the main physiological inhibitor of neutrophil elastase, were at greater risk of developing emphysema (10,11). Subsequently, various studies reported the induction of emphysema in animal models following instillation of NSPs.…”
mentioning
confidence: 99%
“…However, it is well recognised that in a population of heavy smokers only 15-20% of subjects develop COPD [3]. The reason for this is unknown; however, it is likely that individual genetic risk factors may play an important role [4,5].…”
mentioning
confidence: 99%